Continued lessons from the INS gene: an intronic mutation causing diabetes through a novel mechanism. Issue 9 (22nd June 2015) - Carmody, David; Park, Soo-Young; Ye, Honggang; Perrone, Marie E; Alkorta-Aranburu, G; Highland, Heather M; Hanis, Craig L; Philipson, Louis H; Bell, Graeme I; Greeley, Siri Atma W
Abstract : Background: Diabetes in neonates usually has a monogenic aetiology; however, the cause remains unknown in 20–30%. Heterozygous INS mutations represent one of the most common gene causes of neonatal diabetes mellitus. Methods: Clinical and functional characterisation of a novel homozygous intronic mutation (c.187+241G>A) in the insulin gene in a child identified through the Monogenic Diabetes Registry (http://monogenicdiabetes.uchicago.edu ). Results: The proband had insulin-requiring diabetes from birth. Ultrasonography revealed a structurally normal pancreas and C-peptide was undetectable despite readily detectable amylin, suggesting the presence of dysfunctional β cells. Whole-exome sequencing revealed the novel mutation. In silico analysis predicted a mutant mRNA product resulting from preferential recognition of a newly created splice site. Wild-type and mutant human insulin gene constructs were derived and transiently expressed in INS-1 cells. We confirmed the predicted transcript and found an additional transcript created via an ectopic splice acceptor site. Conclusions: Dominant INS mutations cause diabetes via a mutated translational product causing endoplasmic reticulum stress. We describe a novel mechanism of diabetes, without β cell death, due to creation of two unstable mutant transcripts predicted to undergo nonsense and non-stop-mediated decay, respectively. Our discovery may have broader implications for those with insulin deficiency later in life.